ANALYSIS OF THE ROLE OF STAKEHOLDERS IN SOCIAL REHABILITATION PROGRAMS AT THE CLASS II A NARCOTICS CORRECTIONAL INSTITUTION IN JAKARTA - Alvin Hanif Yusron Sabila; Naniek Pangestuti (Universitas Nusa Cendana, 2026)
This study aims to analyze the role of stakeholders in the implementation of the Social Rehabilitation Program at the Class IIA Narcotics Correctional Institution, as well as to identify the challenges encountered in its implementation. Using a qualitative case study approach, the findings show that the program involves both internal and external stakeholders. Internal stakeholders include institutional leaders, rehabilitation staff, and internal counselors, while external stakeholders consist of organizations such as the National Narcotics Agency, professional counselors, partner foundations, and inmates’ families. Each stakeholder contributes according to their respective roles and responsibilities, creating complementary interactions that support the rehabilitation process. However, the implementation of the program still faces several challenges, including irregular activity schedules, limited inmate mobility, low participation or motivation among inmates, security considerations, and incomplete facilities. These obstacles affect the overall effectiveness of the rehabilitation process. The study concludes that the success of social rehabilitation programs depends not only on policy design but also on the quality of collaboration and coordination among stakeholders. Strengthening cooperation, improving facilities, and enhancing program management are essential to optimize rehabilitation outcomes. Keywords: Social Rehabilitation; Stakeholders; Drug Rehabilitation Centers; Role